2004
DOI: 10.1103/physrevlett.92.037201
|View full text |Cite
|
Sign up to set email alerts
|

Mn Interstitial Diffusion in(Ga,Mn)As

Abstract: We present a combined theoretical and experimental study of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
283
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(298 citation statements)
references
References 26 publications
14
283
0
1
Order By: Relevance
“…The XAS/XMCD arising from Mn-1 has been associated to a mixed-valence ground state due to the large Mn 3d hybridization with the surrounding 4sp states. 19,24,25 Numerical calculations indicated a mixed 80% d 5 -20% d 6 L ground state ͑L is a ligand hole͒. 24,25 In Mn-AP, both the energy shift of the XMCD minimum and the line shape suggest a different valence state with lower occupancy of the 3d levels, implying a lowering of the d 6 character and increment of the d 5 one.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XAS/XMCD arising from Mn-1 has been associated to a mixed-valence ground state due to the large Mn 3d hybridization with the surrounding 4sp states. 19,24,25 Numerical calculations indicated a mixed 80% d 5 -20% d 6 L ground state ͑L is a ligand hole͒. 24,25 In Mn-AP, both the energy shift of the XMCD minimum and the line shape suggest a different valence state with lower occupancy of the 3d levels, implying a lowering of the d 6 character and increment of the d 5 one.…”
Section: Methodsmentioning
confidence: 99%
“…The latter configuration has a more structured XAS spectrum, located at higher BE with respect to the d 4 -d 5 -d 6 one. [19][20][21][22] A recent detailed study on the depth concentration of Mn in ͑Ga,Mn͒As reveals the presence of Mn with d 5 configuration up to 6 nm from the interface, coexisting with Mn Ga and not related to oxide. 23 Results in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In these configurations Mn is highly mobile [7] and tends to accumulate on the surface during crystal growth, resulting in non uniform doping profiles and Mn enriched surfaces. Thermal treatments on thin films in gaseous environment, or on As-capped samples [8], are used to remove Mn I thus improving the ferromagnetic properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Mean-field theories based on this scenario have captured the increase of ferromagnetic transition temperature, T c , with doping and other macroscopic properties of Ga 1-x Mn x As 5,6 . Experimental efforts have also shown that improved material quality, achieved through various methods including annealing of random alloy samples, can significantly increase T c even above 150 K [7][8][9][10] . However, currently missing is an accurate microscopic picture, which identifies the precise nature of hole states involved and provides clues on how to enhance ferromagnetism in this compound.…”
mentioning
confidence: 99%
“…The significance of the experiments is perhaps best realized by considering the separations between Mn acceptors in randomly doped Ga 1-x Mn x As at concentrations required for the highest reported ferromagnetic temperatures [7][8][9][10] . At 5% doping, 98% of the Mn dopants have one or more neighbour within the sixth nearest-neighbour or closer.…”
mentioning
confidence: 99%